INTERSECTING MARGINS: REPRESENTATIONS OF BLACK DISABILITY AND ECONOMIC PRECARITY IN SELECTED CONTEMPORARY AMERICAN LITERATURE - Wahid Kaiser; Asadul Al Galif; Tamanna Ferdous; Md. Ziaul Haque (PARADIGM: Journal of Language and Literary Studies, 2025)
This paper examines the intersections of race, class, and disability in contemporary American literature through Toni Cade Bambara’s The Salt Eaters and Jesmyn Ward’s Salvage the Bones. It considers how both novels represent Black, disabled, and economically precarious subjects while challenging dominant narratives of normalcy, productivity, and social value in U.S. society. Drawing on intersectional feminist literary criticism and critical disability studies, the study employs qualitative close reading and thematic analysis to examine characterization, narrative voice, embodiment, and communal resistance. The findings suggest that both authors frame disability not as an isolated medical condition but as a social, political, and historical formation shaped by racism, poverty, gendered vulnerability, and structural neglect. Bambara foregrounds psychic distress and communal healing within Black political struggle, whereas Ward represents embodied precarity and survival amid environmental disaster and systemic poverty. Together, the novels challenge ableist and neoliberal assumptions by emphasizing care, cultural memory, interdependence, and collective endurance. This research contributes to scholarship on African American literature and disability studies by demonstrating the importance of intersectionality in literary analysis and by positioning literature as a crucial site for political imagination, resistance, and the revaluation of marginalized lives.